2013
DOI: 10.1016/j.linged.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Time travel: The role of temporality in enabling semantic waves in secondary school teaching

Abstract: Based on the theoretical understandings from Legitimation Code Theory (Maton, 2013) and Systemic Functional Linguistics (Martin, 2013) underpinning the research discussed in this special issue, this paper focuses on classroom pedagogy to illustrate an important strategy for making semantic waves in History teaching, namely temporal shifting. We begin with a brief contextualisation of how Legitimation Code Theory (LCT) and Systemic Functional Linguistics have been used together to investigate cumulative knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 4 publications
0
22
0
6
Order By: Relevance
“…) at different levels of analysis (from national curriculum to individual texts) using a range of methods (documentary analysis, surveys, interviews, etc.). Empirical studies applying LCT conceptual tools can be found in educational technology (Carvalho & Goodyear, 2014a, 2014bHoward & Maton, 2011), engineering (Wolff & Luckett 2013), history (Matruglio, Maton, & Martin, 2013), journalism (Kilpert & Shay, 2013), music (Lamont & Maton, 2010), physics (Georgiou, Maton, & Sharma, 2014) and many other fields. In the rest of this article, we use the concepts to explore the organising principles of four disciplines of design -engineering, architecture, digital media, and fashion -through the analysis of interviews and survey with designers.…”
Section: Analysing Knowledge Practices: Legitimation Code Theory (Lct)mentioning
confidence: 99%
“…) at different levels of analysis (from national curriculum to individual texts) using a range of methods (documentary analysis, surveys, interviews, etc.). Empirical studies applying LCT conceptual tools can be found in educational technology (Carvalho & Goodyear, 2014a, 2014bHoward & Maton, 2011), engineering (Wolff & Luckett 2013), history (Matruglio, Maton, & Martin, 2013), journalism (Kilpert & Shay, 2013), music (Lamont & Maton, 2010), physics (Georgiou, Maton, & Sharma, 2014) and many other fields. In the rest of this article, we use the concepts to explore the organising principles of four disciplines of design -engineering, architecture, digital media, and fashion -through the analysis of interviews and survey with designers.…”
Section: Analysing Knowledge Practices: Legitimation Code Theory (Lct)mentioning
confidence: 99%
“…Por ejemplo, para los estudiantes que no dominan este recurso en la enseñanza secundaria, el acceso a un discurso que depende menos del contexto se ve seriamente afectado. Sin el dominio de este tipo de discurso no podrán acceder al conocimiento específico de la materia que aparece en los libros de texto, los ejemplarios o la web, y no podrán demostrar que dominan este conocimiento al momento de ser evaluados (Martin y Maton, 2013). Este tipo de problema educativo requiere una perspectiva amplia que, como mínimo, incorpore el componente textual e ideacional al concepto de presencia, de modo de poner en juego muchas de las variables que son relevantes.…”
Section: Dependencia Contextual En Todas Las Metafuncionesunclassified
“…ej., Martin, Maton y Matruglio, 2010). En años más recientes, en el marco de un proyecto interdisciplinario centrado en la construcción de conocimiento en las clases de historia y ciencia en escuelas secundarias (Freebody, Martin y Maton, 2008;Martin y Maton, 2013), el trabajo de Maton (2013aMaton ( , 2013b sobre la noción de "gravedad semántica" ha vuelto a despertar el interés por la variable de modo. Para Maton, una manera de introducir el concepto de "gravedad semántica" es por medio de las ideas de Bernstein (2000), quien hacía hincapié en la relación que se establece entre las prácticas de construcción de conocimiento y su contexto social y simbólico.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Todas estas investigaciones se enfocan en la relevancia asignada a la descripción de la mediación docente para ayudar a los estudiantes a desempaquetar y reempaquetar nuevamente los conceptos más abstractos y alejados del sentido común (Matruglio et al, 2013). El objetivo de esta práctica social reside en evitar un aprendizaje memorístico y favorecer la construcción del conocimiento a través de una pedagogía explícita y de la configuración de significados por medio de diferentes opciones semióticas.…”
Section: Introductionunclassified